2017
DOI: 10.1001/jamainternmed.2017.0311
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Characteristics of Paid Malpractice Claims Among US Physicians by Specialty, 1992-2014

Abstract: IMPORTANCEAlthough physician concerns about medical malpractice are substantial, national data are lacking on the rate of claims paid on behalf of US physicians by specialty.OBJECTIVE To characterize paid malpractice claims by specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 37 publications
6
141
2
Order By: Relevance
“…A recent analysis of all paid malpractice claims in the US National Practitioner Data Bank (NPDB) between 1992 and 2014 found that diagnostic error was the most common type of allegation 4. In a study published in 2013, Saber Tehrani et al summarised 25 years of diagnostic error claims in ambulatory and hospital settings, and concluded that diagnostic errors were the most common, costly and dangerous type of medical mistake 5.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of all paid malpractice claims in the US National Practitioner Data Bank (NPDB) between 1992 and 2014 found that diagnostic error was the most common type of allegation 4. In a study published in 2013, Saber Tehrani et al summarised 25 years of diagnostic error claims in ambulatory and hospital settings, and concluded that diagnostic errors were the most common, costly and dangerous type of medical mistake 5.…”
Section: Introductionmentioning
confidence: 99%
“…Annual malpractice from the beginning of 2006 to the end of 2016 varied between 0 and 5% generally, while the rate of the annual complaints in the same period varied between 0 and 45%, in which in contrast to the results of Studdert et al's study in USA (Studdert et al, 2006). This rate indicates that the complaints of patients against physicians and therapeutic staff are ascending annually, but the percentage of physician accusations and also paid malpractice payment amount have not significantly increased (Schaffer et al, 2017) (Fig. 3).…”
Section: Discussionmentioning
confidence: 65%
“…When we analyzed the causes of medical error in surgery it was observed that the typification of the most frequent errors according to the perception of the surgical team are errors due to negligence and recklessness as it is also described by authors as (Schaffer et al, 2017;Tingle, 2016;López Ordoñez et al, 2004;Tempelaar, 1997;Dewees et al, 1991). Even these authors propose the paradox that the greater the clinical experience, the greater the probability of making mistakes, perhaps due to overconfidence, which increases the impact of lawsuits on hospital costs (Pérez, 2019;Tingle, 2016;López Ordoñez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This same study mentions that the most predominant processes are: The penal ones, followed by the ethical and civil ones, although it can originate that all the processes are activated simultaneously, without forgetting that a process can begin up to 20 years after the attention, whereas the levels of complexity more compromised in processes of medical responsibility are the II and III respectively (López Ordoñez et al, 2004). In the United States 40% of physicians are involved in responsibility processes during their professional practice as described by Daley J. Harrington J., cited by (López Ordoñez et al, 2004), but the actual national data on the rate of claims paid on behalf of U.S. physicians by specialty is still unknown (Schaffer et al, 2017) In Colombia, the most frequent sanctions are those applied for violation of Law 23 of 1981 on medical ethics, which includes issues such as dedication of sufficient time to the patient, the quality of the medical history and submission to unjustified risks in which while it is true that to err is human, it is also the fact of adopting measures and precautions so that mistakes do not occur in which the principle of non-maleficence is applied from the Hippocratic oath of Primum Non Nocere: above all, do no harm! (Smith, 2005)…”
Section: Introductionmentioning
confidence: 99%